Pancasila Value-Based Humanist Law in Order to Revitalize Ideology at the Global Level - Mangesti, Yovita Arie (Law Research Review Quarterly, 2016)
One model of legal thought in Indonesia is the Progressive legal discourse that proposes how to rule with conscience, which involves personal predisposition in overcoming legal problems confined to rule and text-based traditions. Dynamics of the development of the global value system has an impact on the emergence of various interpretations of values ​​that are used as a foundation in overcoming various legal issues in various fields of life. In line with the mission to reform the law from the legitimacy of the rule and text based, we need a legal model with the strengthening of the state ideology as a parameter for progressive punishment. Through a conceptual approach and an eclectic approach to the value of Pancasila as a rechtsidee and fundamental norm, this paper proposes the concept of Humanist Law Based on Pancasila Value, with postulates: a). uphold human dignity and dignity as the image of the creator (human dignity as "Imago Dei"); b). rule with a conscience to protect vulnerable people (vulnerable people); c). leads to justice; d). responsive and antisiative. The overall postulate is a frame work that aims to achieve legal objectives, namely justice, certainty and expediency. This concept of Humanist Law reflects the character building of the Indonesian nation, which is qualified and competent to participate in building global civilization.